On double convergence in measure - Gökhan, A. (Academic Press, 2015)
In this paper, we define some modes of convergence in the Pringsheim's sense for a double sequence (fmn) of measurable functions. We also give the relations between modes of these convergences. © 2015 Academic Publications, Ltd.
Keywords: Convergence in measure; Double limit; Double sequence